Direct conversion of cellulose to high-yield methyl lactate over Ga-doped Zn/H-nanozeolite Y catalysts in supercritical methanol. Issue 8 (27th March 2017) - Verma, Deepak; Insyani, Rizki; Suh, Young-Woong; Kim, Seung Min; Kim, Seok Ki; Kim, Jaehoon
Abstract : For realizing sustainable bio-based refineries, it is crucial to obtain high yields of value-added chemicals via direct conversion of cellulose and lignocellulosic biomass. Abstract : For realizing sustainable bio-based refineries, it is crucial to obtain high yields of value-added chemicals via the direct conversion of cellulose and lignocellulosic biomass. Although the conversion of cellulose using homogeneous catalysts has been demonstrated to be quite successful, low cellulose conversion and poor product selectivity have been observed using heterogeneous catalysts. In this study, for the first time, the efficient conversion of cellulose to lactic acid derivatives, which can be used as a green solvent and a potential precursor for fine chemicals and biodegradable polymers, over a Ga-doped Zn/H-nanozeolite Y (Ga-doped Zn/HNZY) catalyst is described. Under optimized conditions at 280 °C in supercritical methanol, methyl lactate (ML) and methyl 2-methoxypropionate (MMP) are obtained in yields of 57.8% and 12.8%, respectively, from cellulose; these values are greater than those reported in previous studies conducted using heterogeneous catalysts. Using oakwood, ML and MMP are obtained in yields of 12.3% and 18.6%, respectively. A large external surface area of the HNZY support and the synergistic effect of Ga doping on ZnO enhance Lewis acid sites with the simultaneous decrease of the Brønsted acid sites. This unique catalyst (Ga-doped Zn/HNZY) is beneficial for controlling the consecutive reaction pathways of the decomposition of cellulose to glucose, retro-aldol condensation to trioses, and intramolecular Cannizzaro reaction to ML.